Intense upconversion luminescence and energy‐transfer mechanism of Ho3+/Yb3+ co‐doped SrLu2O4 phosphor. Issue 8 (21st April 2017) - Liu, Songbin; Ye, Xinyu; Liu, Shuifu; Chen, Mengyao; Niu, Hu; Hou, Dejian; You, Weixiong
Abstract: A series of novel SrLu2 O4 : x Ho 3+, y Yb 3+ phosphors ( x =0.005‐0.05, y =0.1‐0.6) were synthesized by a simple solid‐state reaction method. The phase purity, morphology, and upconversion luminescence were measured by X‐ray diffraction (XRD), scanning electron microscopy (SEM), and photoluminescence (PL) spectroscopy. The doping concentrations and sintering temperature were optimized to be x =0.01, y =0.5 and T =1400°C to obtain the strongest emission intensity. Under 980 nm laser diode excitation, the SrLu2 O4 :Ho 3+, Yb 3+ phosphors exhibit intense green upconversion (UC) emission band centered at 541 nm ( 5 F4, 5 S2 → 5 I8 ) and weak red emission peaked at 673 nm ( 5 F5 → 5 I8 ). Under different pump‐power excitation, the UC luminescence can be finely tuned from yellow‐green to green light region to some extent. Based on energy level diagram, the energy‐transfer mechanisms are investigated in detail according to the analysis of pump‐power dependence and luminescence decay curves. The energy‐transfer mechanisms for green and red UC emissions can be determined to be two‐photon absorption processes. Compared with commercial NaYF4 :Er 3+, Yb 3+ and common Y2 O3 :Ho 3+, Yb 3+ phosphors, the SrLu1.49 Ho0.01 Yb0.5 O4 sample shows good color monochromaticity and relatively high UC luminescence intensity. The results imply that SrLu2 O4 :Ho 3+, Yb 3+ can be a good candidate for green UC material in display fields.